KARAKTERISTIK REKAHAN ALAMI, STUDI KASUS MODEL SINGKAPAN DIGITAL (DOM) BATUAN GRANITIK DI MUARO SILOKEK, SUMATERA BARAT - Koesmawardani, Wildan Tri; Nurshal, M.E. Marshal; Sapiie, Benyamin; Rudyawan, Alfend (Fakultas Ilmu dan Teknologi Kebumian (FITB), Institut Teknologi Bandung (ITB), 2019)
Digital Outcrop Model (DOM) is a method of building a more realistic, 3D-based geocellular model based on photogrammetric data. DOM can describe position of fractures with a minimum length of four meters, so it can describe better distribution and fracture geometry with more precision. DOM used has a dimension of 320 m Ã— 12 m at fractured granitic rock outcrops at Muaro Silokek, West Sumatra. There are 1183 fracture interpretations in the DOM. Based on the fracture orientation scattered in the DOM, there are four segmentation structures with three domain orientation directions, north north west - south southeast (NNE-SSW), northeast - southwest (NE-SW), and east-northeast - west southwest (ENE-WSW). The results of kinematic analysis of the structural data show that the Muaro Silokek area is affected by the strike slip fault with the northwest-southeast direction (NW_SE) which is parallel with orientation of the Takung Fault. Fracture density analysis in DOM was carried out by grid method with grid dimensions of 20 m Ã— 20 m resulting in a value range of 0.15 - 1 fracture/m2. From the results of the fracture density analysis, the kinematic analysis can be carried out to determine the minor fault orientation. Fracture density is strongly influenced by the distance to fault and has logarithmic distribution data with a high correlation coefficient R2 = 0.98.